What makes for an effective stop-smoking service?. Issue 10 (27th June 2011) - Brose, Leonie S; West, Robert; McDermott, Máirtín S; Fidler, Jennifer A; Croghan, Emma; McEwen, Andy
Abstract : Background: The English network of stop-smoking services (SSSs) is among the best-value life-preserving clinical intervention in the UK NHS and is internationally renowned. However, success varies considerably across services, making it important to examine the factors that influence their effectiveness. Methods: Data from 126 890 treatment episodes in 24 SSSs in 2009–10 were used to assess the association between intervention characteristics and success rates, adjusting for key smoker characteristics. Treatment characteristics examined were setting (eg, primary care, specialist clinics, pharmacy), type of support (eg, group, one-to-one) and medication (eg, varenicline, single nicotine replacement therapy (NRT), combination of two or more forms of NRT). The main outcome measure was abstinence from smoking 4 weeks after the target quit date, verified by carbon monoxide concentration in expired air. Results: There was substantial variation in success rates across intervention characteristics after adjusting for smoker characteristics. Single NRT was associated with higher success rates than no medication (OR 1.75, 95% CI 1.39 to 2.22); combination NRT and varenicline were more successful than single NRT (OR 1.42, 95% CI 1.06 to 1.91 and OR 1.78, 95% CI 1.57 to 2.02, respectively); group support was linked to higher success rates than one-to-one support (OR 1.43, 95% CI 1.16 to 1.76); primary care settings were less successful than specialist clinics (OR 0.80, 95% CI 0.66 to 0.99). Conclusions: Routine clinic data support findings from randomised controlled trials that smokers receiving stop-smoking support from specialist clinics, treatment in groups and varenicline or combination NRT are more likely to succeed than those receiving treatment in primary care, one-to-one and single NRT. All smokers should have access to, and be encouraged to use, the most effective intervention options.